PENGARUH MODEL PEMBELAJARAN SAINTIFIK TERHADAP KREATIVITAS ANAK USIA 5-6 TAHUN - Baiq Nada Buahana; Filsa Era Sativa (Jurnal Pendidikan Sang Surya, 2024)
This research aims to determine the influence of the scientific learning model on the creativity of children aged 5-6 years at Al-Fadhillah Kindergarten. This type of experimental research with a quantitative approach uses a quasi-experimental design with a pre-test post-test control group design. There were 30 research subjects aged 5-6 years with 15 students each from class B1 (Experimental class) and class B2 (Control class). Data collection methods are by observation and documentation. The data analysis technique uses the independent sample t test technique. Based on the results of the research that has been carried out, the results show that there is an influence of the scientific learning model on creativity. This can be seen from the t test that has been carried out, the result is t = 24.509 > t table = 0.688 and a significance value (2-tailed) of 0.000 < 0.05, then it can be concluded that the hypothesis is accepted. This means that there is a difference between students' creative abilities for pre-test and post-test data, so it can be concluded that there is an influence of the scientific learning model on creativity in children aged 5-6 years at Al-Fadhillah Kindergarten.